Research progress on the mechanism of long non-coding RNA LINC00641 in the development of malignant tumors - GUO Mengmeng; MING Daojing; REN Yiming; QIAN Xinhang; YANG Shisong; WANG Congcong; LU Peiwen; ZHANG Jinhui; YUAN Shuai; XI Shu; ZENG Xiantao (Yixue xinzhi zazhi)
Long non-coding RNAs (lncRNAs) are a class of functional RNA that is not translated into proteins, with more than 200 nucleotides in length. LncRNAs are involved in the regulation of gene expression at the transcriptional, and post-transcriptional levels. In recent years, more and more evidence has shown that lncRNAs regulate the biological processes of tumor proliferation, apoptosis, invasion and metastasis by various signaling pathways. LINC00641, located on human chromosome 14q11.2, is differentially expressed in a variety of tumors tissues and is associated with prognosis of tumor. Changes in the expression of LINC00641 can lead to alterations in various biological behaviors of tumor cells. Therefore, LINC00641 could be a new biomarker and potential target in clinical practice. We reviewed the biological function, molecular mechanism and clinical significance of LINC00641 in various human malignant tumors.